Mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes syndrome (MELAS): diagnostic criteria, features of epileptic seizures, and treatment approaches by the example of a clinical case - M. A. Yamin; I. V. Chernikova; L. V. Araslanova; P. A. Shevkun (Неврология, нейропсихиатрия, психосоматика, 2017)
The paper describes a patient with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes syndrome (MELAS). The features of  the course and therapy of epilepsy in MELAS are discussed. The disease  is known for its late diagnosis when years elapse from the onset of the  clinical manifestations to diagnosis. The paper presents clinical criteria  for the diagnosis of MELAS and the specific features of brain neuroimaging changes that allow identification of the disease at an early stage.